Conceptual Design Framework for Sustainable Structures - Kulasuriya, Chandana; Vimonsatit, Vanissorn (Khavaran Institute of Higher Education, 2012)
This paper presents an overview of philosophical underpinnings of the discourse of sustainable structures. The world view that have been influenced by the scientific revolution occurred in modern era considers reality as a single external objective entity and hence sustainability is viewed from an objective angle. Accordingly the discourse of sustainable structures revolved around resource efficiency, new technologies, etc., but do not traverse much through other forms of realities, namely, subjective reality and inter-subjective reality such as aesthetic sustainability. Post-modernism that emerged as a reaction to modernism recognises other forms of realities as well. However, even within post-modern discourse other forms of realities are not recognised in a total integrated way. In the dawn of the new millennium, Post-postmodern era has begun, and it not only recognises multiple realities, but also integrates those realities in a complementary way. Within the Post-postmodern movement, American Philosopher Ken Wilber is a leading figure who introduced 'Integral Theory' and 'All Quadrants All Levels Framework' (AQAL Framework). This paper explores the possibility of employing the AQAL general framework for sustainable structures to develop a more specific framework that integrates many aspects of sustainability such as material sustainability and aesthetic sustainability. The paper will present how the developed AQAL framework can be used for brain storming during the conceptual design stage of civil engineering structures.